2014
DOI: 10.1371/journal.pone.0094615
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 1.5 Tesla MRI and Anesthetic Regimen Concerning Cardiac Analysis in Mice with Cardiomyopathy

Abstract: Accurate assessment of left ventricular function in rodent models is essential for the evaluation of new therapeutic approaches for cardiac diseases. In our study, we provide new insights regarding the role of a 1.5 Tesla (T) magnetic resonance imaging (MRI) device and different anesthetic regimens on data validity. As dedicated small animal MRI and echocardiographic devices are not broadly available, we evaluated whether monitoring cardiac function in small rodents with a clinical 1.5 T MRI device is feasible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
7
1
1
Order By: Relevance
“…We finally evaluated cardiac function parameters including LVEF and SVI. Despite a clear deterioration of EAM mice in comparison to healthy controls of a previous study,[ 23 ] cardiac function parameters did show a moderate but not significant correlation with sVCAM-1.…”
Section: Discussioncontrasting
confidence: 65%
“…We finally evaluated cardiac function parameters including LVEF and SVI. Despite a clear deterioration of EAM mice in comparison to healthy controls of a previous study,[ 23 ] cardiac function parameters did show a moderate but not significant correlation with sVCAM-1.…”
Section: Discussioncontrasting
confidence: 65%
“…CINE MRI was carried out by using an electrocardiographic‐triggered FLASH CINE gradient‐spoiled gradient echo sequence with the following parameters: flip angle = 15°; repetition time = 8 ms; echo time = 2.5 ms; field of view = 35 mm × 35 mm; matrix size = 192 × 192; in‐plane spatial resolution = 0.182 × 0.182 mm 2 per pixel; slice thickness = 1 mm; number of average = 6; and heart cycle sampled with 20 images. After the acquisition, morphological parameters of interest for cardiac function were measured in diastole and systole (Bakermans et al, 2015; Grabmaier et al, 2014). In particular, left end diastolic volume (EDV) and left end systolic volume (ESV) were manually measured.…”
Section: Methodsmentioning
confidence: 99%
“…also observed this effect and demonstrated that isoflurane anesthesia was associated with increased myocardial blood flow in Wistar rats compared with pentobarbital 16 . However, accumulating evidence favors the use of isoflurane in rodent cardiac imaging studies, such as a preclinical report highlighting the superiority of isoflurane anesthesia based on lower inter-subject variability of CMR left ventricular parameters compared with intraperitoneal anesthesia with MMF combination (medetomidine, midazolam and fentanyl) 20 . Our results provide additional evidence for the use of isoflurane to reduce the test-retest variability of left ventricular volume assessment when two CMR examinations are performed one week apart in the same healthy animals.…”
Section: Discussionmentioning
confidence: 99%